Perilaku Mahasiswa Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Bung Hatta Dalam Pencarian Informasi Untuk Pemenuhan Kebutuhan Informasi di Perpustakaan Universitas Bung Hatta - Sanjaya, Riyan; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper focuses on the needs and behavior of searching to information Department of Economics student who is doing a thesis. This study aims to determine the information needs and information retrieval needs. This paper is useful for Bung Hatta University Libraries to determine the information needs of students of Department of Economics. This study used a qualitative research approach. Data were collected through direct interviews with user who come to visit the space scientific Bung Hatta University Library at 08:30 until 10:30 GMT on 4 to July 5, 2012. Analyzing the data be descriptive. By analyzing the data, it was concluded the following. First, the sources of information used most often students of Department of Economics University of Bung Hatta is in the form of text books. Department of Economics Students visit the library in order to make or complete the thesis. Collection of books for the Department of Economics at the Bung Hatta University Library does not meet the need. The book takes students are books written with the Indonesian language. Second, information retrieval can be seen through the strategy used. Students stated that if the information sought is not found in the Library of the University of Bung Hatta, the measures taken or the student is to go visit the bookstore and visit the local library. Furthermore, the use of any tools, most of the students in finding information in the library is that they go directly to the collection with a look for yourself to rack collection. Keywords: need and behavior of searching; information needs